GEO-AR ENHANCEMENT: Inovasi Pembelajaran Berbasis Augmented Reality pada Guru Geografi di SMA/MA Kota Padang Panjang - Bayu Wijayanto; Bigharta Bekti Susetyo; Suci Fitria Rahmadani; Jefri Pernando; Sukron Operma (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
During the COVID-19 pandemic, learning is carried out online. Online innovation-based learning is very different from conventional learning that occurs in schools. Teachers and students are not face to face but remotely, allowing teachers and students to be in different places, with different commitments and skills in operating technology. On the other hand, learning competencies must be owned by students. “Framework for 21st Century Learning” describes four competencies or fields that students must master which include 1) core subjects and 21st century themes, 2) learning and innovative skills, 3) information, media and technology skills and 4) life and career skills. The problems found in the field are the lack of innovation in geography learning media, both face-to-face and online and the low utilization of technology by geography teachers at SMA/MA Padang Panjang City. The limitations of learning tools owned by students are problematic themselves. High school students have smartphones with limited capacity, so they are only ideal for using mobile learning. Technology must be used strategically to benefit students. Based on these conditions, the service team felt the need to contribute in overcoming these problems, it needed a training to develop innovative learning media based on Augmented Reality (AR) and the use of platforms or MOOCs in geography subjects. The training is project-based, meaning that the end of the training is the formation of Augmented Reality-based geography learning media that can be used by teachers in learning. The implementation of this PKM will be a solution to the problems faced by geography teachers regarding the use of Augmented Reality (AR)-based technology in geography learning.